2007
DOI: 10.1152/ajpgi.00496.2006
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of function and localization of tight junctional structures and Mrp2 in sustained estradiol-17β-d-glucuronide-induced cholestasis

Abstract: Estradiol-17beta-D-glucuronide (E(2)17G) induces immediate and profound but transient cholestasis in rats when administered as a single bolus dose. Here, we examined the consequence of sustained E(2)17G cholestasis and assessed the function and localization of the tight junctional proteins zonula occludens-1 (ZO-1) and occludin and of the canalicular transporter multidrug resistance-associated protein-2 (Mrp2). An initial dose of E(2)17G (15 mumol/kg iv) followed by five subsequent doses of 7.5 mumol/kg from 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…While the elevation of CYP7A1 expression is possibly due to the ablation of FXR together with its negative feedback on bile acid synthesis. In this study, we observed remarkable down-regulation of FXR and elevated expression of CYP7A1, MRP2, MRP3 in EEFP-treated female groups, suggesting the endogenously accumulation of bile acids which is reflected by the increase of serum bile acids (Kast et al, 2002;Mottino et al, 2007;Rost et al, 1999Rost et al, , 2008.…”
Section: Discussionsupporting
confidence: 49%
“…While the elevation of CYP7A1 expression is possibly due to the ablation of FXR together with its negative feedback on bile acid synthesis. In this study, we observed remarkable down-regulation of FXR and elevated expression of CYP7A1, MRP2, MRP3 in EEFP-treated female groups, suggesting the endogenously accumulation of bile acids which is reflected by the increase of serum bile acids (Kast et al, 2002;Mottino et al, 2007;Rost et al, 1999Rost et al, , 2008.…”
Section: Discussionsupporting
confidence: 49%
“…After fixation, liver slices were incubated overnight with the specific antibodies to Abcb11, Abcc2, and occludin, and this was followed by 1 hour of incubation with the appropriate cyanine 2-conjugated or cyanine 3-conjugated donkey anti-IgG. Occludin staining was carried out to demarcate the limits of the canaliculi [7], [36]. All images were taken with a Nikon C1 Plus confocal laser scanning microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Previous in vitro studies have shown that progesterone and estradiol influence TJ expression in a concentration-dependent manner in human vascular endothelial and human endometrial epithelial cells [6,29] . However, animal studies concentrated on TJ proteins, like occludin or ZO-1, and data of claudin-1 are almost entirely missing [3] . It is thought that claudin-1 could be regulated via different signal transduction pathways like MAPkinase or PI3ki-nase [9] ; however, the data are not consistent and it will be interesting to consider these pathways in the context of nongenomic TH action.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune thyroiditis is the most common cause of hypothyroidism in humans, and a female preponderance in both autoimmune thyroid disease and hypothyroidism has long been known [1,2] . The incidence of developing hypothyroidism in the Western world ranges between 0.6 and 3.5 per 1,000 people [3] . In Europe women are 1.7-to 6.8-fold more frequently affected by hypothyroidism than men [1,2] .…”
Section: Introductionmentioning
confidence: 99%